PARTISIPASI MASYARAKAT DALAM PEMBUATAN RUMAH KACA (GREEN HOUSE) SEBAGAI SARANA PEMBENIHAN BERWAWASAN EKOEDUWISATA DI KEBUN BUAH BENDOSARI - Widiakongko, Priyagung Dhemi (UIN Sunan Kalijaga, 2023)
The construction of a greenhouse as a nursery facility with an ecotourism perspective has been carried out at the Bendosari Orchard, Sumbersari Moyudan, Sleman. The purpose of making this greenhouse is as a means of seeding fruit plants which are a source of income for the Bendosari Orchard, namely guava and avocado and as a tourist attraction to attract more visits to the fruit garden. This research was carried out using the Rural Rapid Appraisal (RRA) approach with 6 stages, namely socialization, interviews, workshops on equalizing perceptions about fruit plant breeding using the grafting method and about greenhouses, surveys of prospective greenhouse construction locations, workshops on planning and building greenhouses and home supervision. glass. With this research, the perception and awareness of garden managers regarding fruit plant nurseries has increased as proven through questionnaires and the success of building a Greenhouse at the Bendosari Orchard. Apart from that, park managers have also realized the need to build greenhouses independently. The greenhouse that was built was made of galvalum, UV plastic and insect-proof glass. This is done to maintain ecological aspects in the greenhouse and in the Bendosari Orchard.